Highly selective and sensitive coumarin–triazole‐based fluorometric 'turn‐off' sensor for detection of Pb2+ ions. (2nd March 2018) - Shaily,; Kumar, Ajay; Parveen, Iram; Ahmed, Naseem
Abstract: Exposure to even very low concentrations of Pb 2+ is known to cause cardiovascular, neurological, developmental, and reproductive disorders, and affects children in particular more severely. Consequently, much effort has been dedicated to the development of colorimetric and fluorescent sensors that can selectively detect Pb 2+ ions. Here, we describe the development of a triazole‐based fluorescent sensorL5 for Pb 2+ ion detection. The fluorescence intensity of chemosensorL5 was selectively quenched by Pb 2+ ions and a clear color change from colorless to yellow could be observed by the naked eye. ChemosensorL5 exhibited high sensitivity and selectivity towards Pb 2+ ions in phosphate‐buffered solution [20 mM, 1:9 DMSO/H2 O (v/v), pH 8.0] with a 1:1 binding stoichiometry, a detection limit of 1.9 nM and a 6.76 × 10 6 M −1 binding constant. Additionally, low‐cost and easy‐to‐prepare test strips impregnated with chemosensorL5 were also produced for efficient of Pb 2+ detection and proved the practical use of this test.